2017
DOI: 10.1371/journal.pone.0187879
|View full text |Cite
|
Sign up to set email alerts
|

A simple way for targeted delivery of an antibiotic: In vitro evaluation of a nanoclay-based composite

Abstract: The sodium-modified form of fluorohectorite nanoclay (NaFh) is introduced as a potential drug carrier, demonstrating its ability for the controlled release of the broad-spectrum antibiotic Ciprofloxacin through in vitro tests. The new clay-drug composite is designed to target the local infections in the large intestine, where it delivers most of the incorporated drug thanks to its pH-sensitive behavior. The composite has been conceived to avoid the use of coating technology and to decrease the side-effects com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 47 publications
0
8
0
1
Order By: Relevance
“…Furthermore, HNTs-Ht nanomaterial could be an alternative system for the simultaneous co-delivery of different antibacterial agents for the treatment of different patologies. It, indeed presents similar adsorption behavior of other systems commonly used, such as bentonite, fluorohectorite, montmorillonite, and hydroxyapatite, for the delivery of ciprofloxacin and silver ions [ 27 , 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, HNTs-Ht nanomaterial could be an alternative system for the simultaneous co-delivery of different antibacterial agents for the treatment of different patologies. It, indeed presents similar adsorption behavior of other systems commonly used, such as bentonite, fluorohectorite, montmorillonite, and hydroxyapatite, for the delivery of ciprofloxacin and silver ions [ 27 , 28 , 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 68%
“…It has been demonstrated that the capture of CIPRO by FHt is more efficient at acidic than neutral environments, with FHt capturing up to 0.49 g of CIPRO per gram of FHt, and highly inefficient capture at alkaline conditions [52,56,57,58,59,60] . There is substantial evidence pointing out that the capture of APIs at low pH occurs mainly via cation exchange, with the drug molecules replacing the interlamellar cation and acting in its place to maintain the charge balance of the FHt particles [52,56,58] .…”
Section: Ii2 Fluorohectorite For Drug Deliverymentioning
confidence: 99%
“…Despite CIPRO's capture ability at neutral environments, the higher efficacy in acidic conditions indicates that the ionic nature of the API is an important parameter to be considered when preparing the clay-drug composites [56] . Furthermore, release studies demonstrated that the drug release is slow, pH-dependent, controlled and thermally activated [52,58] * Regarding toxicity of FHt and FHt-drug composites, in vivo and in vitro studies demonstrated that FHt is not harmful, even when it has Li + as interlamellar cation [58,59] . Additionally, the effectiveness of FHt-CIPRO against important human pathogens, such as E. coli and P. aeruginosa, remained the same as the effectiveness of CIPRO alone.…”
Section: Ii2 Fluorohectorite For Drug Deliverymentioning
confidence: 99%
“…There are several cases investigated and reported in the literature with respect to capturing and retention mechanisms for encapsulation of foreign molecules inside such clay interlayers ( Fig. 6), including H 2 O intercalation [12,13,[39][40][41][42][43][44][45][46], CO 2 capture and retention [36,[47][48][49][50][51], cation exchange [12,13,52], medical drug capture and release [12,13,39,[53][54][55][56][57][58][59], capture of surfactants [12,13,39,60,61], polymers [12,13,39,[62][63][64], or nanoparticles [65]. These encapsulation properties of clay nanolayered stacks are crucial for several engineering applications, e.g.…”
Section: Fig 2 Adopted From Supplementary Informationmentioning
confidence: 99%